Measurement of nitric oxide (NO) generation rate by chloroplasts employing electron spin resonance (ESR) - Galatro, Andrea Verónica (2016)
Chloroplasts are among the more active organelles involved in free energy transduction in plants (photophosphorylation). Nitric oxide (NO) generation by soybean (Glycine max, var ADM 4800) chloroplasts was measured as an endogenous product assessed by electron paramagnetic resonance (ESR) spin-trapping technique. ESR spectroscopy is a methodology employed to detect species with unpaired electrons (paramagnetic). This technology has been successfully applied to different plant tissues and subcellular compartments to asses both, NO content and generation. The spin trap MGD-Fe2+ is extensively employed to efficiently detect NO. Here, we describe a simple methodology to asses NO generation rate by isolated chloroplasts in the presence of either L -Arginine or nitrite (NO2 −) as substrates, since these compounds are required for enzymatic activities considered as the possible sources of NO generation in plants.